النمذجة بمساعدة الحاسوب وإيجاد الأبعاد المثلى لتصميم مولد AC فائق الناقلية - حايك, غسان (Latakia University Journal -Engineering Sciences Series, 2019)
نقدم في هذا البحث إمكانية الاستفادة من الطرق المنطقية بغية الوصول إلى الاستغلال الأمثل لمولد (Alternating Current) AC فائق الناقلية، حيث طورت طريقة جديدة في التصميم تهدف إلى تحقيق هذه الغاية من خلال برنامج حاسوبي يحدد بشكل منهجي بارامترات التصميم لمكونات الآلة، مع توصيف لحزمة البرامج من خلال بنية منطقية تراعي استخدام طريقة هوك – جيفيس (Hook-Jeeves) ونماذج نيلدر - ميد(Nelder-Mead). ثم تقديم أنموذج عددي لتبيان فعالية التصميم مرفقاً بنموذج تحليلي يحدد سرعة الجزء الدوار من الآلة، دون إغفال باقي الخصائص الأخرى. استخدمت نتائج الطريقة كمحددات للأداء الميكانيكي، كما قدمت نماذج تحليلية لأداء آلات أخرى على شكل خصائص حدية للناقل فائق الجودة. The feasibility of applying rational methods to a superconducting generator design is presented. A new method of designing is developed which permits the optimization of a superconducting generator to take place. The method is used in a computer program package which systematically determines the optimum design parameters of machine components. The optimization techniques and the logical structure of the computer package are described. The optimization problem is solved by using the interior penalty function method – a penalty function in which the direct search methods of Hook-Jeeves and Nelder-Mead are used. A numerical example demonstrating the effectiveness of the program is given. A new analytical method is also presented for the prediction of the inner rotor bursting speed, taking into account geometry, applied stresses, and material properties. The results of this method are used as mechanical performance constraints. Moreover, an analytical presentation of other machine performances such as the critical characteristics of the superconductor is also presented.